2009
DOI: 10.1007/s12031-009-9299-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of AP-2α Transcription Factor in the Regulation of Synapsin II Gene Expression by Dopamine D1 and D2 Receptors

Abstract: Synapsins are a family of neuron-specific phosphoproteins involved in synaptic vesicle docking, synaptogenesis, and synaptic plasticity. Previous studies have reported an increase in synapsin II protein by dopaminergic agents in the striatum, medial prefrontal cortex, and nucleus accumbens. This study investigated the mechanistic pathway involved in synapsin II regulation by dopaminergic drugs using primary midbrain neurons to determine which of several transcription factors regulates synapsin II expression. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…The presynaptic protein synapsin II has shown significant involvement in the etiology of schizophrenia, and previous studies from our lab have linked modulation of this protein to activation of dopamine receptors [10,41]. The current study shows that a significant increase in synapsin IIa expression occurs in dopaminergic regions strongly implicated in schizophrenia, including the striatum, mPFC, and NAc, following chronic administration of PAOPA.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The presynaptic protein synapsin II has shown significant involvement in the etiology of schizophrenia, and previous studies from our lab have linked modulation of this protein to activation of dopamine receptors [10,41]. The current study shows that a significant increase in synapsin IIa expression occurs in dopaminergic regions strongly implicated in schizophrenia, including the striatum, mPFC, and NAc, following chronic administration of PAOPA.…”
Section: Discussionsupporting
confidence: 66%
“…Regulation of synapsin II expression has previously been shown to occur by modulation of the dopamine D1 and D2 receptors [10,41]. In this current study, increases in synapsin IIa were observed in dopamine rich regions, including the striatum, NAc and mPFC.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations